Future humans : inside the science of our continuing evolution - Solomon, Scott (New Haven : Yale University Press, 2016)
"Evolutionary biologist Scott Solomon draws on the explosion of discoveries in recent years to examine the future evolution of our species. Combining knowledge of our past with current trends, Solomon offers convincing evidence that evolutionary forces still affect us today. But how will modernization--including longer lifespans, changing diets, global travel, and widespread use of medicine and contraceptives--affect our evolutionary future?" --publisher description.
Genomes and germs -- Big data -- World in transition -- Sex -- Small partners -- Beyond the horizon.
Includes bibliographical references (pages 185-212) and index.
Keywords: Human evolution; Human evolution; Evolution (Biology); Behavior evolution; Biological Evolution; Hominidae; Behavior evolution; Evolution (Biology); Human evolution; Human evolution -- Forecasting; Evolution; Mensch; Zukunft